A KILAU SEHAT : KREATIVITAS INOVATIF MEMANFAATKAN LAHAN DAN TANAMAN UNTUK KESEHATAN - Dwi Aryani, Wulan (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
SMP Negeri 1 Kandeman has a very large area of land that needs to be optimized. Taking advantage of this situation, the school implements the "KILAU SEHAT" Project for Strengthening the Profile of Pancasila Students, which stands for Creative Innovation Utilizing Land and Ginger Plants for Health. The objectives of this Best Practice are: 1) How is the implementation of the KILAU SEHAT Project for Strengthening the Profile of Pancasila Students (P5) by utilizing the school's land and processing the harvest?; 2) What is the impact of the KILAU SEHAT P5 Project on Students? The method used in this best practice is STAR (Situation, Challenge, Action, and Reflection). The results of the Best Practice show that: 1) The KILAU SEHAT P5 can be implemented in schools, where students can optimize the school's land by planting ginger, and the harvest is processed into healthy ginger powder drinks. The impact of the KILAU SEHAT P5 on students includes: 1) Increased awareness among students and all school elements about the importance of maintaining and utilizing the environment productively, 2) Gaining valuable entrepreneurial experience, 3) Achieving the strengthening of the Pancasila Student Profile, particularly in the dimensions of faith and piety to God Almighty, noble character, collaboration, and creativity. Keywords: utilizing land, ginger plants, ginger powder